2005
DOI: 10.2136/sssaj2004.0104
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Arya and Paris Water Retention Model for Brazilian Soils

Abstract: The Arya and Paris (AP) model predicts soil water retention curves from soil particle‐size distribution (PSD) data based on the similarity between these two functions. The AP model estimates pore radius (ri) from the radius (Ri) of spherical particles by scaling pore length with a parameter α. This paper evaluates the performance of the AP model with representative Brazilian soil types using three constant α values: α = 1.38, 0.938 (literature values), and 0.977, (obtained in the present work); and a α‐variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
0
48
0
4
Order By: Relevance
“…In this semi-physical approach, pore radii were determined by scaling the pore lengths of cubic close-packed assemblages with spherical particles to those of the natural structure. Researchers thereafter have suggested that the SWCC prediction by the AP model would improve if the scaling parameter (a) were formulated as a varying rather than a constant value over soil particle ranges and textural classes (Basile and D'Urso, 1997;Arya et al, 1999;Vaz et al, 2005). The AP model has been progressively modified and used to predict SWCC.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…In this semi-physical approach, pore radii were determined by scaling the pore lengths of cubic close-packed assemblages with spherical particles to those of the natural structure. Researchers thereafter have suggested that the SWCC prediction by the AP model would improve if the scaling parameter (a) were formulated as a varying rather than a constant value over soil particle ranges and textural classes (Basile and D'Urso, 1997;Arya et al, 1999;Vaz et al, 2005). The AP model has been progressively modified and used to predict SWCC.…”
Section: à3mentioning
confidence: 99%
“…(3) is the scaling parameter. Basile and D'Urso (1997) and Vaz et al (2005) expressed a values as functions of h and h, respectively. To decrease the uncertainty in the SWCC prediction caused by the interdependence of a on h or h, we adopted the formulation proposed by Arya et al (1999), that is,…”
Section: Arya and Paris Modelmentioning
confidence: 99%
“…Another method suggested by the same researcher and also adopted by (S. Liu, et al, 2013) for the estimation of is to linear fit between and as follows: (12) The constant values of the scale factor obtained by constant method and the linear parameter and, ( that obtained by the above methods are shown in Table (2). (Vaz et al 2005), appraise the performance of the AP model by employing an expression for as a function of the soil volumetric water content, (θ); as (13) The aforementioned scaling methods have been utilized in association with the Arya and Paris algorithm for estimation the soil water characteristic curve relationships for the soil specimens of Zakho city.…”
Section: Estimation Of Scaling Factors : -mentioning
confidence: 99%
“…The AP procedure introduced an empirical parameter, α, used to scale pore attributes from hypothetical formations to natural structures. Arya and Paris (1981) initially determined α as constant, whereas several researchers have suggested that variable α would improve the predictions of the SWCC (Basile and D'Urso, 1997;Arya et al, 1999;Vaz et al, 2005). Fractal concepts have also been used to derive α (Tyler and Wheatcraft, 1989).…”
Section: Introductionmentioning
confidence: 99%